Deteksi Serangan SQL Injection pada Website dengan Menggunakan Metode Reguler Expression: Deteksi Serangan SQL Injection pada Website dengan Menggunakan Metode Reguler Expression - Reni Supartini (Progressive Information, Security, Computer, and Embedded System, 2023)
Along with current technological developments, security for data information residing on websites is very vulnerable to crimes in the internet world such as attacks on security holes in the database layer or often known as SQL Injection. SQL Injection attack is a method to insert SQL commands as input through an application in order to gain access to the database. This attack can find out usernames, passwords, and other data that is in the database. So that the SQL Injection attack is one of the most popular attacks and is often used to take advantage of security holes in the system because of how easy it is to use it. If the website database can be accessed, then a hacker can easily steal various confidential data, can even manipulate or damage data on the website. This article aims to test the effectiveness of SQL Injection attacks using the regular expression method. The results of research on effectiveness in SQL Injection are the accuracy of database search time and the accuracy of information from the database.